The Time Has Come . . . to Talk of Many Things Charleston Conference Proceedings, 2019 (Purdue University Press, 2020)
Presentations from the 39th annual Charleston Library Conference (held November 4-8, 2019) are included in this annual proceedings volume. Major themes of the meeting included open educational resources, analysis and assessment of collections and library users, changes in licensing practices, virtual reality/augmented reality, journal package options, the future of print collections, and open access publishing. While the Charleston meeting remains a core one for acquisitions librarians in dialog with publishers and vendors, the breadth of coverage of this volume reflects the fact that this conference continues to be one of the major venues for leaders in the publishing and library communities to shape strategy and prepare for the future. Almost 2,000 delegates attended the 2019 meeting, ranging from the staff of small public library systems to the CEOs of major corporations. This volume provides a rich source for the latest evidence-based research and lessons from practice in a range of information science fields. The contributors are leaders in the library, publishing, and vendor communities.